The Effect Of Regional Original Income (Pad) And General Allocation Fund (Dau) On Economic Growth In South Sulawesi Province - Hasrini Hakim Hasrini (Income Journal Of Economics Development, 2021)
This study aims to determine the effect of capital expenditure and local revenue ( on economic growth in South Sulawesi. This type of research used in this research is quantitative research. The data processed is secondary data from capital expenditures, local revenue and economic growth in South Sulawesi Province in 2011-2020. The results showed that simultaneously capital expenditures and local revenue have a significant effect on economic growth in the province of South Sulawesi, this is as evidenced by the significance value greater than the significance probability (0.004 > 0,05) and partially local revenue has a significant effect on economic growth in South Sulawesi, as evidenced by the significance value is smaller than the significance probability (0.012 < 0,05), this is evidenced by the significance General Allocation Fund than the probability (0.468 > 0.05). Partially capital expenditure does not have a significant effect on economic growth in South Sulawesi.